2001
DOI: 10.1084/jem.194.8.1171
|View full text |Cite
|
Sign up to set email alerts
|

Cd11c+B220+Gr-1+ Cells in Mouse Lymph Nodes and Spleen Display Characteristics of Plasmacytoid Dendritic Cells

Abstract: Human plasmacytoid dendritic cells (pDCs) are major producers of IFNα, are activated by CpG motifs, and are believed to enter lymph nodes (LNs) via L-selectin dependent extravasation across high endothelial venules. To identify a similar murine DC type, CD11c+ cells in the LNs of L-selectin–deficient and control BALB/c mice were compared, revealing a population of CD11c+CD11b− cells that is reduced 85% in the LNs of L-selectin–deficient mice. These cells are Gr-1+B220+CD19−, either CD4+ or CD8+, and localize w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
513
3
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 631 publications
(549 citation statements)
references
References 30 publications
26
513
3
4
Order By: Relevance
“…39 MoDCs restored highaffinity LFA-1 after migration to the lymph nodes (Figure 2c), suggesting a role for CCL21 in this process. Interestingly, lymph node-resident human DCs also express endogenous CCL21 on the cell surface, further highlighting the relevance of our study in the in vivo situation.…”
Section: Ccl21 Strongly Binds To Dcs and Induces Active Lfa-1mentioning
confidence: 89%
“…39 MoDCs restored highaffinity LFA-1 after migration to the lymph nodes (Figure 2c), suggesting a role for CCL21 in this process. Interestingly, lymph node-resident human DCs also express endogenous CCL21 on the cell surface, further highlighting the relevance of our study in the in vivo situation.…”
Section: Ccl21 Strongly Binds To Dcs and Induces Active Lfa-1mentioning
confidence: 89%
“…Human pDC have been found clustered around high endothelial venules (HEV) [46]. This anatomical localization and cell surface antigen expression on pDC suggest that pDC migrate from the blood to the lymph nodes through HEV in an L-selectin-dependent manner [47][48][49]. However, it has been reported that CCR7 expression is up-regulated on pDC in response to pathogenic stimuli, and that pDC migrate to the CCR7 ligands CCL19 and CCL21 expressed by stromal cells in the T cell zone and in HEV [29,50,51].…”
Section: Validation Of Pdc Conversion Into Cdcmentioning
confidence: 96%
“…An important cytokine generated by pDC is type1 interferons (IFN-α/β), which become a characteristic of plasmacytoid DC in both humans and mice [78][79][80]. Mouse lymphoid DC population is characterized by expression of a homodimer of the CD8 molecule.…”
Section: The Roles Of T Regulatory Cells and Dendritic Cells In Ibds mentioning
confidence: 99%